2х + 3у = 8
3х + 2у = 7
Решение
Х = ( 8 - 3у ) : 2
Х = 4 - 1,5у
3( 4 - 1,5у ) + 2у = 7
12 - 4,5у + 2у = 7
- 2,5у = - 5
у = 2
Х = 4 - 3 = 1
Ответ ( 1 ; 2 )
5 ^ ( 3x + 1 ) = 25
5 ^ 3x = 25 : 5
5 ^ 3x = 5
3x = 1
x = 1/3
В первом примере взять в скобки (95 : 5)
Получится выражение : 413 * 17 + 97* (95 : 5) = 8864
1) 95 : 5 = 19
2) 413 * 17 = 7021
3) 97 * 19 = 1843
4) 7021 + 1843 = 8864
-----------------------------------------
Во втором примере удалить скобки
Получится выражение: 512 * 3159 - 844 - 2215 : 5 = 1616121
1) 512 * 3159 = 1617408
2) 2215 : 5 = 443
3) 1617408 - 844 = 1616564
4) 1616564 - 443 = 1616121